2016
DOI: 10.1093/ejo/cjw055
|View full text |Cite
|
Sign up to set email alerts
|

3D dentofacial photogrammetry reference values: a novel approach to orthodontic diagnosis

Abstract: 1. When using the proposed method for orthodontic diagnosis, male and female patients should be compared to their respective dentofacial standards. 2. Validation of the proposed method and standards on an orthodontic population is underway to determine the scope its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 47 publications
1
30
0
3
Order By: Relevance
“…Craniofacial assessments and diagnoses involve various diagnostic tools such as clinical photographs and study models to assess the positions and relations of various landmarks of head, jaws and teeth . Multiple medical and dental specialties including orthodontics, plastic surgery, and oral and maxillofacial surgery often depend on comprehensive facial evaluations by measuring facial structures relative to landmarks in the cranial base . 3D photogrammetry could be a potentially valuable tool in these specially, as it allows for analysis of frontal views, while it can be also rotated, translated and zoomed, providing realistic analyses as well as potential outcomes of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Craniofacial assessments and diagnoses involve various diagnostic tools such as clinical photographs and study models to assess the positions and relations of various landmarks of head, jaws and teeth . Multiple medical and dental specialties including orthodontics, plastic surgery, and oral and maxillofacial surgery often depend on comprehensive facial evaluations by measuring facial structures relative to landmarks in the cranial base . 3D photogrammetry could be a potentially valuable tool in these specially, as it allows for analysis of frontal views, while it can be also rotated, translated and zoomed, providing realistic analyses as well as potential outcomes of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Steps for registering the dental and facial images. From Masoud et al 28 values were adjusted to determine statistical significance. Since 14 outcomes were evaluated when comparing traditional cephalometric measurements to 3D photogrammetry measurements, a P value ,.004 was deemed to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary teeth were registered to the smiling 3D facial image using at least 6 common landmarks, including the incisal and gingival embrasures. 28 The smiling and nonsmiling images were registered using the centers of the pupils, the endocanthal points, the highest points on the brow lines, and the mesial and lateral limits of the eyebrows as documented by Masoud et al 28 Figure 1 shows the registration process described previously. The 3D dental casts were digitized with landmarks described by Huanca Ghislanzoni et al 29 The facial landmarks were identified according to Plooij et al 22 and Farkas et al 30 After registration and digitization using a custom version of Facial Insight 3D (Motion View Software), measurements were generated using the eyes and the natural head position as references.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found most diagnostic and treatment decisions reached fair agreement between the two records. Masoud et al 10 established male and female reference values of 3D dentofacial photogrammetry for orthodontic diagnosis. Castillo et al 11 investigated the correlation between nonradiographic 3D photogrammetry measurements and corresponding traditional cephalometric measurements, suggesting that 3D photography was a significant predictor of the cephalometric measurements.…”
Section: Introductionmentioning
confidence: 99%